FERNAND POUILLON’S ATYPICAL ARCHITECTURE: A VISIONARY AND INNOVATIVE APPROACH - Gueliane Nora; Mohammedi Louiza (International Journal of Innovative Technologies in Social Science, 2024)
The article was written based on the memoirs of architect Fernand Pouillon, the research and work by specialists such as Roger Lacroix, Eugène Freyssinet, Yvan Delemontey, and others, as well as on the site visit inspection report that we conducted for projects located in the city of Algiers. It highlights the different approaches of prefabrication in architecture, showcasing Pouillon’s projects and innovations in the field. The article emphasizes the importance of simplicity of forms and structures, as well as the impact of industrialization on the architectural production of the time. Concrete examples of projects and construction methods are cited to illustrate the concepts discussed. How did Pouillon contribute to the evolution of construction methods and the rise of prefabrication in the context of post-war reconstruction? What were its main challenges and criticisms of the architectural practices of its time? This research demonstrates that Pouillon’s work has significantly contributed to the evolution of construction methods by promoting prefabrication and exploring new constructive systems. His criticisms of the practices of the time highlighted the importance of technological innovation and economic efficiency in architecture. In conclusion, his legacy in the field of construction lies in his ability to combine tradition and modernity to meet the challenges of his time, thus influencing the architecture of the period of reconstruction and paving the way for new constructive approaches.